Toundra - Loiselle, Richard (Mnémothèque Internationale des Sciences et Arts en Musique Électroacoustique, 1997)
Recording of Richard Loiselle's Toundra. This work is an homage to the Inuit, a Northern Canadian indigenous group, and the hardships that come with living in the tundra. The composer uses recordings of the Inuit's specialized throat-singing called "katajjait" throughout the work.